Activation of the default network during a theory of mind task predicts individual differences in agreeableness and social cognitive ability. - Udochi, Aisha L.; Blain, Scott D.; Sassenberg, Tyler A.; Burton, Philip C.; Medrano, Leroy; DeYoung, Colin G. (Cognitive, Affective & Behavioral Neuroscience, 2022)
Social cognitive processes, such as emotion perception and empathy, allow humans to navigate complex social landscapes and are associated with specific neural systems. In particular, theory of mind (ToM), which refers to our ability to decipher the mental states of others, is related to the dorsal medial prefrontal cortex and temporoparietal junction, which include portions of the default network. Both social cognition and the default network have been linked to the personality trait Agreeableness. We hypothesized that default network activity during a ToM task would positively predict social cognitive abilities and Agreeableness. In a 3T fMRI scanner, participants (N = 1050) completed a ToM task in which they observed triangles displaying random or social (i.e., human-like) movement. Participants also completed self-report measures of Agreeableness and tests of intelligence and social cognitive ability. In each participant, average blood oxygen level dependent responses were calculated for default network regions associated with social cognition, and structural equation modeling was used to test associations of personality and task performance with activation in those brain regions. Default network activation in the dorsal medial subsystem was greater for social versus random animations. Default network activation in response to social animations predicted better performance on social cognition tasks and, to a lesser degree, higher Agreeableness. Neural response to social stimuli in the default network may be associated with effective social processing and could have downstream effects on social interactions. We discuss theoretical and methodological implications of this work for social and personality neuroscience.